An Organocatalytic Azide–Aldehyde [3+2] Cycloaddition: High‐Yielding Regioselective Synthesis of 1, 4‐Disubstituted 1, 2, 3‐Triazoles1. (30th July 2014) - Ramachary, Dhevalapally B.; Shashank, Adluri B.; Karthik, S.
Abstract An organocatalytic azide–aldehyde [3+2] cycloaddition (organo‐click) reaction of a variety of enolizable aldehydes is reported. The organo‐click reaction is characterized by a high rate and regioselectivity, mild reaction conditions, easily available substrates with simple operation, and excellent yields with a broad spectrum of substrates. It constitutes an alternative to the previously known CuAAC, RuAAC, and IrAAC click reactions.